Permanent magnet shape optimization method for PMSM air gap flux density harmonics reduction - Liu, Chengsi; Xu, Yongxiang; Zou, Jibin; Yu, Guodong; Zhuo, Liang (CES Transactions on Electrical Machines and Systems, 2021)
This paper proposed a permanent magnet optimization method to suppress the air gap flux density harmonic of permanent magnet synchronous motor (PMSM). The method corrected the effective air gap length of the motor, calculated the magnetization length of the permanent in the case of parallel magnetization, and took the influence of the permanent magnet relative permeability into consideration. Based on these works, for a given sinusoidal air gap flux density waveform, the corresponding structural parameters can be calculated, so as to achieve the optimization of the permanent magnet. By using this method to optimize the shape of the magnet, the fundamental wave of the air gap flux density can be retained to the greatest extent, so as to eliminate harmonics and maintain the output capacity at the same time. The feasibility and accuracy of the method have been verified by finite element analysis (FEA) and prototype machine experiment. This method is simple and time-saving, and has a satisfactory accuracy, which provides a reference method for permanent magnet optimization of PMSM.